HISTORY AND MAIN OUTPUTS OF CRYPTOGAMS STUDY IN THE GREEN BELT OF FENNOSCANDIA WITHIN MURMANSK REGION - Кожин, Михаил Николаевич; Боровичев, Евгений Александрович; Белкина, Ольга Александровна; Давыдов, Денис Александрович; Денисов, Дмитрий Борисович; Исаева, Людмила Георгиевна; Константинова, Надежда Алексеевна; Мелехин, Алексей Валерьевич; Попова, Ксения Борисовна; Урбанавичюс, Геннадий Пранасович; Химич, Юлия Ростиславовна; Kozhin, Mikhail; et al. (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2019)
The studies of cryptogams in the Green Belt of Fennoscandia (GBF) within Murmansk Region are reviewed and summarized. This territory, important in terms of biodiversity conservation, encompasses 13 operating protected areas, yet remains insufficiently studied. At first, since the mid-19th century, Finnish scientists played the key role in detecting the cryptogam biota of the GBF. They organized and carried out field surveys, as well as further taxonomic identifications and treatments of individual groups. Later, in the 20th century, intensive studies of cryptogams were associated with economic developments in the region, the establishment and activities of biological institutions in Murmansk Region: Polar-Alpine Botanical Garden-Institute and Institute of North Industrial Ecology Problems of the Kola Science Centre, Russian Academy of Sciences, science departments of strict nature reserves. At the beginning of the 21st century, Forest Research Institute and Institute of Biology of the Karelian Research Centre RAS became involved in the studies. The research mostly focused on the general biodiversity exploration of the territory, but at the same time some new taxa were discovered within various groups of organisms. An analysis of the current state of knowledge shows that algae and fungi in the GBF within Murmansk Region have been studied rather fragmentarily, and the known species composition does not reflect their real diversity. Lichens, mosses and liverworts of the territory have been revealed to a much greater extent. The Pasvik Strict Nature Reserve, the Ainov Islands of Kandalakshsky Strict Nature Reserve, the Nature Park The Rybachy and the Sredny Peninsulas and the regional nature reserve (zakaznik) Kutsa are the best studied areas, and the bulk of the cryptogam diversity of the GBF is concentrated there.